1990
DOI: 10.1111/j.1600-0447.1990.tb01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 levels in serum and cerebrospinal fluid of people with Alzheimer's disease

Abstract: Vitamin B12 levels in the serum and the cerebrospinal fluid (CSF) were compared between patients with Alzheimer's disease (AD) and senile dementia of Alzheimer's type (SDAT) (AD group) and patients with multi-infarct dementia (MID group). The B12 levels in the serum and the CSF were 742 +/- 359 pg/ml and 28 +/- 7 pg/ml (mean +/- SD), respectively, in the AD group, and 962 +/- 254 pg/ml and 50 +/- 26 pg/ml, respectively, in the MID group. CSF B12 levels were significantly lower in the AD group than in the MID g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 4 publications
1
17
0
1
Order By: Relevance
“…[y32P]2N3ATP (specific activity, [5][6][7][8][9][10][11][12][13][14] mCi/,tmol) was then prepared and purified as described for ['t-32P]8N3ATP. Protein molecular size standards were from Bio-Rad.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[y32P]2N3ATP (specific activity, [5][6][7][8][9][10][11][12][13][14] mCi/,tmol) was then prepared and purified as described for ['t-32P]8N3ATP. Protein molecular size standards were from Bio-Rad.…”
Section: Methodsmentioning
confidence: 99%
“…Amyloid, paired helical filament, and a1-antichymotrypsin immunoreactivity have been reported to be elevated in the CSF of AD patients (4)(5)(6). The CSF has also been examined for concentration changes in neuropeptides (7), biogenic amines and their metabolites (8), amino acid or amino acid derivatives (9), vitamins (10), and trace elements (11). However, none of these compounds has emerged as a reliable marker for AD.…”
mentioning
confidence: 99%
“…Earlier reports have shown that cobalamin deficiency is common in dementia disorders [4][5][6][7][8]. Recent studies indicate that decreased levels of cobalamin and folate might increase the risk of developing AD [42], and that increased plasma Hcy is an independent risk factor for the development of dementia disorders [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is even more common in subjects with dementia [4][5][6][7][8]. The means of diagnosing cobalamin deficiency is still a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Low content of cobalamin in CSF was observed in a group of patients with cerebral atrophy [24], Van Tiggelen et al [15] reported low cobalamin levels in alcohol dementia and DAT, but normal levels in multi-infarct dementia (MID). They postulated that zinc deficiency could be an important contributor to the dichotomy observed with normal serum levels and low CSF content of cobalamin [25], Ikeda et al [26] found lower CSF levels of cobal amin in DAT patients as compared to patients with MID. Recently, normal content of CSF cobalamin in DAT was reported, but decreased levels in a group of patients, where no further diagnosis than dementia could be set [27],…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%